AI AND ETHICS: MOVING TOWARDS A FUTURE WHERE AI BENEFITS – RATHER THAN DESTROYS – HUMANITY - Fenton, Adam James; Monett, Dagmar (Universitas Swadaya Gunung Jati, 2023)
2023 may be remembered as the year that Artificial Intelligence (AI) hit the headlines for its potential to transform the economy, society, and humanity. With the launch of OpenAI’s ChatGPT, the wider public experienced first-hand what is it like to interact with an AI that shows remarkably human-like responses in one-to-one conversations. This is a technology with the potential for profound (both negative and positive) impacts on all aspects of human activity from business to politics, justice, education, arts, science, medicine, and virtually any other field of human endeavour. The challenges, as many academics, practitioners, observers, and some legislatures have realised, are in the capabilities of the underlying technology and in regulating AI and ensuring that its deployment and use are ethical, responsible, and trustworthy; that it is used for good rather than evil, to benefit humanity rather than destroy or damage it. However, given both the complexity of the technology itself and the competing vested interests of the many interested parties involved, this is a task which is much easier said than done. Indeed, some commentators have noted that the cursory nature with which ethics has been approached by some actors in the AI regulation debate has been nothing more than “ethics washing” (Metzinger, 2019a, 2019b; van Maanen, 2022) or even “ethics theatre” (Cath & Jansen, 2021). Simply articulating what is meant by “ethical AI” is a task freighted with intercultural challenges, as one may ask “whose ethics are we referring to?” Ethical systems vary through history and across cultures, making it difficult, if not impossible, to articulate a “universal” form of AI ethics. This paper examines the meta-ethical challenges of AI and its regulation and offers novel recommendations to improve discussions and outcomes around the ethics and regulation of contemporary AI. Keywords: Artificial intelligence (AI); AI ethics; AI regulation; intercultural communication and AI; explainable AI; technology; cybersecurity.